Corporate social responsibility and myopic management practice: Is there a link? - DING, Kuan Yong David (Institutional Knowledge at Singapore Management University, 2023)
A Corporate Social Responsibility (CSR)-myopic firm is one that experiences greater-than-normal operating profits but scores worse in its CSR ‘strength’ or ‘concern’ rankings than is normally expected during the same year. We show that myopic behavior in CSR concerns (strengths) are positively (negatively) related to myopia in other conventional discretionary investments such as marketing, R&D, and capital expenditures. We find that large, highly leveraged firms are less likely to be myopic regarding CSR concerns and other discretionary investments; such firms are more likely to engage in myopic behaviors concerning CSR strength. Myopic firms tend to have lower contemporaneous and future risk-adjusted abnormal returns.